EP1132 A comperative molecular analysis of DNA damage response and apoptosis of malignant granulosa cells after exposure to gemcitabine and cisplatin. (1st November 2019) - Vatansever, D; Bildik, G; Taskiran, C; Oktem, O
Abstract : Introduction/Background: We aimed to compare gemcitabine vs. cisplatin in terms of DNA damage response, viability/apoptosis of malignant granulosa cells. Methodology: Malignant granulosa tumour cell lines (COV434 and KGN) were used for the experiments. Cell viability, proliferation, DNA damage response and apoptosis were investigated using immunofluorescence staining and immunoblotting. Cell cycle analysis was carried out using flow cytometry. In vitro oestradiol and AMH productions were analysed by ECLIA method. Gemcitabine and cisplatin were used at four different concentrations corresponding to their therapeutic blood levels. Results: Gemcitabine treatment caused DNA damage, cellular stress, inhibited proliferation and activated cell cycle check-point sensors and induced apoptosis as shown by increased expression of g-histone H2AX, p-JNK, Chk-1/Chk-2, cleaved forms of PARP and caspase-3 in the asynchronous cells in a dose dependent manner. As a result, the proliferation and in vitro AMH and oestrogen production of the cells were decreased at post-exposure 24h. In the cells synchronized at S phase gemcitabine significantly inhibited DNA synthesis and blocked their proliferation. Similar effects were also observed after cisplatin treatment. Exposure of the cells to gemcitabine at G2/M transition abolished the progression of mitosis, caused mitotic arrest and failure to exit mitosis as evidenced by the inhibition of Cyclin B degradation and absence of de-phosphorylation of cdc-2 at Tyr 15 residue. However, such an effect was not observed in the cells synchronized and treated with cisplatin at G2/M. Conclusion: These results may suggest that anti-metabolite chemotherapy drug gemcitabine might have anti-neoplastic actions on granulosa cell tumour. Disclosure: Nothing to disclose